Pembentukan Pemimpin Pelayan Berbasis Komunitas: Implementasi di Organisasi Nirlaba Kristen Mengacu Markus 10:45 dan Gagasan Robert K. Greenleaf - Aimme Reskita; Iteor Tappi' Cia'ba; Theo Lheci; Yuyun Febrianti; Hazaryani Bombongan (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Community-based servant leadership development has emerged as a critical approach for Christian nonprofit organizations seeking to cultivate authentic leaders who embody Christ-centered values. This study explores the integration of theological foundations from Mark 10:45 with Robert K. Greenleaf's servant leadership theory to develop a comprehensive model for leader formation within Christian nonprofit contexts. Employing a qualitative methodology with a library research design, data were collected from scholarly literature and theological sources, then analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. The research reveals a significant alignment between the core message of Mark 10:45—“For even the Son of Man did not come to be served, but to serve”—and the key principles of Greenleaf’s servant leadership, particularly the emphasis on selfless service, empathy, listening, and community building. Community plays a vital role as both a laboratory and an incubator for spiritual and leadership formation, where individuals can internalize leadership values through biblical teaching, mentorship, active religious practices, and shared life experiences. The study proposes a five-stage model: Foundation Building, Community Immersion, Skill Development, Practical Application, and Leadership Multiplication. This model serves as a strategic guide for Christian organizations to intentionally nurture servant leaders. Findings highlight improvements in character formation, organizational effectiveness, and the embodiment of servant leadership traits such as humility, sacrifice, and empathy. The study concludes with practical recommendations for implementation, including structured mentoring systems, the formation of communities of practice, and ongoing evaluation mechanisms. Ultimately, this integrated model supports the mission of Christian nonprofits by shaping leaders who advance both spiritual and social transformation.